THE ROLE OF INTRAUTERINE ANTIGEN EXPOSURE IN THE MORPHOGENESIS OF CEREBRAL BLOOD VESSELS - Reznychenko, Yuriy; Reznychenko, Galyna; Smiian, Kateryna; Mykhalchuk, Oleksandr (Eastern Ukrainian Medical Journal, 2024)
Introduction. The state of cerebral vessels in children of the first year of life with congenital toxoplasmosis, both active and without signs of activity (as models of antenatal antigenic exposure), was considered. The patients were born to mothers whose pregnancy proceeded with mild preeclampsia and perinatal damage to the nervous system. The features of the morphogenesis of the brain vessels of rats after exposure to antigens in the antenatal period were experimentally investigated.Materials and Methods. 119 children of the first year of life were examined. 43 patients with toxoplasmosis, 25 children from women whose pregnancy was complicated by mild preeclampsia, and 28 children with perinatal lesions of the nervous system of hypoxic-ischemic genesis due to antenatal hypoxia of the fetus. The comparison group consisted of 23 healthy children with an uncomplicated antenatal history. Experimental study of the morphogenesis of brain vessels of Wistar rats after intrauterine administration of antigens according to the method of M.A. Voloshin.Results. At 1–2 and 7–8 months of life, in children with antigenic antenatal exposure and perinatal lesions of the nervous system of hypoxic-ischemic genesis, blood flow disorders in the anterior cerebral arteries, vessels of the nail bed, manifestations of endothelial dysfunction and impaired function of the sympathoadrenal system were detected. In the experiment, after the intrauterine introduction of antigens of various nature, an increase in the proportion of the connective tissue component in blood vessels was established, and a significant decrease in the ratio of muscle and connective tissue components from the 1st to the 60th day of postnatal development. Changes in indicators of carbohydrate metabolism and a decrease in glycogen in the anterior cerebral artery of rats 1–60 days of life with antigenic antenatal exposure indicate long-term changes in metabolic disorders of carbohydrate metabolism in the anterior cerebral arteries. By extrapolating the results obtained in the experiment on rats, it is possible to predict metabolic disorders in the vessels of people of the appropriate age, which to a certain extent explains the ultrasound and biomicroscopic changes in vessels, endothelial dysfunction detected in children with antigenic antenatal stimulation at 1–2 and 7–8 months of life.Conclusions. The identified features indicate a change in the morphogenesis of brain vessels after antenatal antigenic exposure and are the background for the formation of central nervous system pathology in children